COMPARATIVE ANALYSIS OF REWARD AND EMPLOYEE PERFORMANCE BASED ON GENDER AT CENTRAL BANK OF BANK SULUT - Oroh, Ryan Vitaly; Lapian, S.L.H.V Joyce; Pandowo, Merinda (Universitas Sam Ratulangi, 2014)
Employee are the big asset of organization. Employee Performance are have big effect of organization performance. The best way to attract employee performance is rewarding employee. Reward can be tangible such money, bonuses or called extrinsic reward and intangible reward such promotion, holiday or called intrinsic reward. The purpose of this research are to analyzed significant differences in employee performance based on reward between male and female. To achieve the objectives researcher use following instrument depend on the extrinsic reward ,intrinsic reward and employee performance. The target of populationÂ were the employees at Central Bank Of Bank Sulut, in North Sulawesi, Indonesia. And the sample take 100 employees of 140 total employees. Data was collected using questionnaire and analyzed using independent sample t test. The result from the study found there are significant differences in employee performance based on reward between male and female. The study recommended the company should know how the company standard use for determine the reward depend on employee performance. Keywords: intrinsic reward, extrinsic reward